(untitled) (Innovative professional education, 2024)
Aspects of the effectiveness of distance education, their research and ways of improvement are considered. Proposed indicators for assessing performance in the context of each aspect. The indicators that measure the effectiveness of distance education are described, taking into account the social responsibility of educational institutions. Approaches to measuring the economic efficiency of education are given. Special attention is paid to the factors on which it depends and the proposed ways of increasing it.